2015
DOI: 10.1007/s00455-015-9602-9
|View full text |Cite
|
Sign up to set email alerts
|

Age-Related Changes in Pharyngeal Lumen Size: A Retrospective MRI Analysis

Abstract: Age-related loss of muscle bulk and strength (sarcopenia) is often cited as a potential mechanism underlying age-related changes in swallowing. Our goal was to explore this phenomenon in the pharynx, specifically, by measuring pharyngeal wall thickness and pharyngeal lumen area in a sample of young versus older women. MRI scans of the neck were retrospectively reviewed from 60 women equally stratified into three age groups (20s, 60s, 70+). Four de-identified slices were extracted per scan for randomized, blind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
48
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 80 publications
(50 citation statements)
references
References 25 publications
2
48
0
Order By: Relevance
“…Swallowing‐related muscles lose mass due to aging and disease, and a loss of muscle mass is associated with reduced swallowing function. Older populations show atrophy in the tongue, as shown by an ultrasound study atrophy in the geniohyoid muscle, as shown by a computed tomography study; and thinning in the pharyngeal wall, as shown by a magnetic resonance imaging study . Furthermore, ultrasound examinations in perioperative patients have shown atrophy in the geniohyoid muscle after surgery; the muscle atrophy of the geniohyoid muscle was significantly prominent in patients who could not recover to their preoperative level of oral intake within 2 weeks after surgery .…”
Section: Mechanisms and Risk Factors Of Dysphagia Caused By Sarcopeniamentioning
confidence: 99%
See 1 more Smart Citation
“…Swallowing‐related muscles lose mass due to aging and disease, and a loss of muscle mass is associated with reduced swallowing function. Older populations show atrophy in the tongue, as shown by an ultrasound study atrophy in the geniohyoid muscle, as shown by a computed tomography study; and thinning in the pharyngeal wall, as shown by a magnetic resonance imaging study . Furthermore, ultrasound examinations in perioperative patients have shown atrophy in the geniohyoid muscle after surgery; the muscle atrophy of the geniohyoid muscle was significantly prominent in patients who could not recover to their preoperative level of oral intake within 2 weeks after surgery .…”
Section: Mechanisms and Risk Factors Of Dysphagia Caused By Sarcopeniamentioning
confidence: 99%
“…Older populations show atrophy in the tongue, as shown by an ultrasound study 36 atrophy in the geniohyoid muscle, as shown by a computed tomography study; 27 and thinning in the pharyngeal wall, as shown by a magnetic resonance imaging study. 37 Furthermore, ultrasound examinations in perioperative patients have shown atrophy in the geniohyoid muscle after surgery; the muscle atrophy of the geniohyoid muscle was significantly prominent in patients who could not recover to their preoperative level of oral intake within 2 weeks after surgery. 38 In acute stroke patients, computed tomography showed decreased muscle mass of the anterior belly of the digastric, geniohyoid and temporalis muscles at the time of hospitalization, which was related to dysphagia; additionally, muscle mass was more decreased with greater age.…”
Section: Mechanisms and Risk Factors Of Dysphagia Caused By Sarcopeniamentioning
confidence: 99%
“…; Molfenter et al . ), and slower pharyngeal transit time (Cook et al . ), all of which can lead to the increased pharyngeal residue observed in elderly individuals (Ekberg and Feinberg ; Cook et al .…”
Section: Swallowing Changes Associated With Agingmentioning
confidence: 99%
“…The increased pharyngeal lumen size observed in elderly individuals (Molfenter et al . ), could potentially lead to increased work load of the pharyngeal constrictors during swallow efforts. Research documenting a longer time to maximum pharyngeal constriction in the elderly (Tracy et al .…”
Section: Swallowing Changes Associated With Agingmentioning
confidence: 99%
See 1 more Smart Citation